Retroperitoneal lipoma, a rare cause of pelvic mass in women - Maliheh Arab; Somayyeh Noei Teymoordash; Maryam Talayeh; Abdolali Ebrahimi; Niloofar Nakhlian; Narges Khatoon Tabatabaei Shoja; Masoomeh Raoufi (Babol University of Medical Sciences, 2021)
Background: Lipoma is a benign mesenchymal tumor of soft tissue that occurs in almost all parts of the body where fat normally exists. Retroperitoneal lipomas are very infrequent condition with about 20 cases represented in the literature since 1980. They usually present as an abdominal mass or with pressure symptoms to adjacent organs. Case Presentation: A 66-year-old, post-menopausal woman referred to Imam Hossein Medical Center due to abdominal pain. Abdominopelvic magnetic resonance imaging (MRI) revealed a large mass containing fat component without enhancement on the right side of the pelvis. Tumor markers were within normal ranges. The patient underwent laparotomy and a 12 cm retroperitoneal mass which was located on the iliopsoas muscle with extension into the inguinal canal was resected with pathology report of lipoma. There has been no recurrence after one year of follow-up since surgery. Conclusion: In the differential diagnosis of retroperitoneal pelvic mass at all ages, lipoma should be considered as a rare cause.